Exploring longitudinal trends and multifactorial correlations of COVID-19 vaccination willingness among healthcare workers in China: a two-phase cross-sectional study before and after the 2023 phase of COVID-19 pandemic - Liu, Xinyu; Li, Lin; Dai, Rongrong; Zheng, Shuhan; Su, Ying; Ding, Lingling; Long, Jianyun; Zhang, Hangjie (Frontiers in Public Health, 2025)
BackgroundHealthcare workers' (HCWs') acceptance of the coronavirus disease 2019 (COVID-19) vaccines constitutes a globally concerned issue, which exhibits variations across different countries and distinct phases of the pandemic. Specifically, the characteristics of HCWs' vaccine acceptance in China following the pre- and post-pandemic period in 2023 remain unclear.MethodsWe conducted a population-based two-phase cross-sectional study in Zhejiang, China. Phase 1 was implemented during the pre-pandemic period (July–September 2022), with the primary objective of investigating HCWs' willingness to receive the fourth dose of COVID-19 vaccine. Phase 2, conducted in the post-pandemic period (November 2023–January 2024), focused on exploring HCWs' willingness to undergo annual COVID-19 vaccination. A total of 1,657 HCWs participated in the survey, where data on demographic characteristics, vaccination history, risk perception, and behavioral factors were collected. Multivariate logistic regression analysis was subsequently performed to identify factors associated with HCWs' vaccination willingness.ResultsIn the first phase (2022, n = 820), 70.61% of participants expressed willingness to receive the fourth dose of the COVID-19 vaccine. Separately, in the second phase (2023, n = 837), the willingness of HCWs to undergo annual COVID-19 vaccination was 28.43%. Concurrently, a substantial decline in HCWs' trust in vaccines was observed: 85.24% of respondents endorsed vaccine safety in 2022, whereas this proportion fell to 57.23% in 2023. Similar downward trends were noted in perceived efficacy (from 78.78% in 2022 to 53.41% in 2023) and vaccine recommendation rates (from 86.10% in 2022 to 56.27% in 2023). Women were less likely to accept a fourth dose [odds ratio (OR) = 0.56, 95% confidence interval (CI): 0.37–0.85]. Laboratory personnel (OR = 3.57, 95% CI: 1.22–10.45) and those confident in vaccine efficacy (OR = 5.06, 95% CI: 1.95–13.08) were more likely to receive a booster. Prior vaccination plus high trust strongly predicted willingness for annual vaccination adherence (OR = 7.23, 95% CI: 4.05–12.92). Despite high primary-series (99.3%) and booster (92.8%) coverage, 7.2% remained unboosted; 33.3% cited lack of awareness and 50% reported contraindications.ConclusionFollowing the COVID-19 pandemic, notable shifts were observed in HCWs regarding their perceptions, acceptance, and recommendation behaviors toward COVID-19 vaccines. Collectively, the observations presented herein provide empirical evidence to inform the optimization of COVID-19 vaccination strategies targeting HCWs.